2023
DOI: 10.2478/auoc-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the inhibitory action of essential oil from Eucalyptus globulus leaves on the corrosion of mild carbon steel in 1M HCl medium

Abstract: The present work aims to valorize an aromatic and medicinal plant of Eucalyptus globulus found in the region of Dakar, Senegal. To do so, we first extracted the essential oil contained in the leaves of the plant harvested in October 2020. We obtained the essential oil by hydrodistillation using a Clevenger type extractor with a yield of 1.70% of the dry plant mass. This value is quite appreciable compared to the different values in the literature. The essential oil extracted from the leaves of Eucalyptus globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Is important to remember that drying methods should be selected considering the active metabolites, plant species, and plant tissues where these molecules accumulate (Caputo et al, 2022;Ozdemir et al, 2018). The drying process has been reported to have a great influence on the chemical constituents and yield of the essential oil of aromatic plants (Bathily et al, 2023). In a study on the effects of hot air drying on OV and RO, the results showed that hot air caused drastic losses in the OV as the essential oils volatilized and the dried product lost quality.…”
Section: Conditioning Of Plant Materialsmentioning
confidence: 99%
“…Is important to remember that drying methods should be selected considering the active metabolites, plant species, and plant tissues where these molecules accumulate (Caputo et al, 2022;Ozdemir et al, 2018). The drying process has been reported to have a great influence on the chemical constituents and yield of the essential oil of aromatic plants (Bathily et al, 2023). In a study on the effects of hot air drying on OV and RO, the results showed that hot air caused drastic losses in the OV as the essential oils volatilized and the dried product lost quality.…”
Section: Conditioning Of Plant Materialsmentioning
confidence: 99%
“…Extracts from different parts of the eucalyptus plant have been studied and affirmed to be effective inhibitors to deter the corrosion of mild steel in different corrosive environments. A study to investigate the inhibitory behaviour of the oil obtained from the eucalyptus globulus leaves has been undertaken [22] It was reported that the application of the oil at 1.6 g/L gave the maximum inhibition efficiency of 89.03 % at room temperature. In addition, the inhibition efficiency was observed to reduce as the temperature increased from 298 to 338 K. The adsorption behaviour of the oil was found to be in sync with the Langmuir adsorption isotherm model.…”
Section: Introductionmentioning
confidence: 99%